Effects of corn supplementation on meat quality and fatty acid composition of Dorper lambs fed PKC-urea treated rice straw - Saeed, Osama Anwer; Sazili, Awis Qurni; Akit, Henny; Ebrahimi, Mahdi; Alimon, Abdul Razak; Samsudin, Anjas Asmara @ Ab Hadi (BioMed Central, 2019)
Background: The increasing costs of feed has subsequently increased the costs of production of livestock, thereby decreasing the profit margin of this sector. The utilization of agro-industrial by-products has to some extent substitute some of the corn grains and soyabean meal, commonly used in animal feeds. In Malaysia, palm kernel cake (PKC) is a by-product of the oil palm industry and is frequently used to supply both crude protein (14–16% CP) and energy (11 MJ/kg) in ruminants. The energy and protein content are adequate for maintenance in the majority of ruminants. However, highly available energy supplementation is known to improve growth performance and protein deposition. This study was carried out to determine the effect on the quality of meat and fatty acid composition of the semitendinosus (ST), supraspinatus (SS), and longissimus lumborum (LL) muscles of Dorper lambs by including corn as an energy source in a basal diet of PKC urea-treated rice straw. Results: The results show that the LL muscle-drip loss was greater in animals supplemented with 5% corn compared to the other groups. Higher pH values of SS and LL muscles were observed in animals supplemented with 5 and 10% corn. Furthermore, the L* value of ST muscle was increased in lambs fed on 5% corn while, reduced in those fed on 0% corn, but the a* and b* values were not significantly different in the treatment groups. The fatty acid composition of the SS muscles showed that lambs fed on 10% corn had higher levels of sum PUFA n-3 compared to those fed on 0% corn. The concentration of C18:1trans11 and CLA c12 t10 in ST muscle from the lambs fed on supplemented diets were higher than those of the controls. Conclusion: This study has concluded the supplementation of corn as a source of energy into a PKC urea-treated rice straw-based diet increased the PUFA concentrations of muscles as compared to control groups.